Interpreting Physics - MacKinnon, Edward. author. aut Link
XIV, 270 p.
Keywords: This book is the first to offer a systematic account of the role of language in the development and interpretation of physics. An historical-conceptual analysis of the co-evolution of mathematical and physical concepts leads ti the classical/quatum interface. Bohrian orthodoxy stresses the indispensability of classical concepts and the functional role of mathematics. We analyze ways of extending and then going beyond this orthodoxy orthodoxy. Finally, the book analyzes how a revised interpretation of physics impacts on basic philosophical issues: conceptual revolutions, realism, and reductionism.